Pregnancy in adolescence and adverse neonatal outcomes in Ecuadorian mestizo newborns - Fabricio González-Andrade; Xavier Saeteros-Cordero (Pediatrics and Neonatology)
Background: To establish the association between pregnancy in early and middle adolescence and adverse neonatal outcomes in Ecuadorian mestizo newborns. Methods: Study design: epidemiological, observational/descriptive, and cross-sectional. Settings: Gynecological and Obstetric Hospital Isidro Ayora at Quito, Ecuador, from July to October of 2018. Participants: this study included 303 newborns and their mothers, 101 children of adolescent mothers between 14 and 16 years old, 101 adolescents between the ages of 17 and 19, and 101 infants born to adult mothers between 20 and 34 years of age. Results: There is no statistically significant association between maternal age, gestation time, neonatal morbidity and APGAR at 5 min. Neonatal morbidity is higher in adolescent mothers residing in rural areas and in these who had fewer than five prenatal check-ups. In the case of mothers with a pathological history, regardless of the area in which they resided, the highest percentages were recorded in the case of mothers of 24–30 years with five or more prenatal appointments, and in adolescent mothers from 14 to 19 years of age with fewer than five prenatal appointments. Indeed, the greater the number of prenatal evaluations the higher the percentage of pathological findings. There is a close relationship between the age of the mother and the number of prenatal check-ups performed during pregnancy. Conclusion: Teenage mothers have a higher percentage of neonatal morbidity in deliveries with gestational age equal to or greater than 37 weeks of gestation and AGPAR 8 and 9 at 5 min. In addition, there were a higher percentage of cases of respiratory failure and sepsis in newborns, especially when fewer than five prenatal examinations were performed. The highest percentage of identified prenatal pathological antecedents occurred in the group of mothers from 20 to 34 years old who attended more than five prenatal controls. Young pregnant women go less frequently to prenatal appointments, particularly in rural areas, and their newborns have a higher percentage of respiratory failure and sepsis. Key Words: pregnancy, early and middle adolescence, adverse neonatal outcomes, ecuadorian, mestizo newborns, public health, sepsis, respiratory insufficiency